Molecular basis of the therapeutic properties of hemorphins. (August 2020) - Ali, Amanat; Alzeyoudi, Seham Abdullah Rashed; Almutawa, Shamma Abdulla; Alnajjar, Alya Nasir; Vijayan, Ranjit
Graphical abstract: Abstract: Hemorphins are endogenous peptides, 4–10 amino acids long, belonging to the family of atypical opioid peptides released during the sequential cleavage of hemoglobin protein. Hemorphins have been shown to exhibit diverse therapeutic effects in both human and animal models. However, the precise cellular and molecular mechanisms involved in such effects remain elusive. In this review, we summarize and propose potential mechanisms based on studies that investigated the biological activity of hemorphins of different lengths on multiple therapeutic targets. Special emphasis is given to molecular events related to renin-angiotensin system (RAS), opioid receptors and insulin-regulated aminopeptidase receptor (IRAP). This review provides a comprehensive coverage of the molecular mechanisms that underpin the therapeutic potential of hemorphins. Furthermore, it highlights the role of various hemorphin residues in pathological conditions, which could be explored further for therapeutic purposes.